The collector ebook A novel. - Silva, Daniel (Gabriel Allon, 2023)
"A world-class practitioner of spy fiction."—Washington Post In this electrifying thriller from #1 New York Times bestselling author Daniel Silva, Gabriel Allon undertakes a search for a stolen Vermeer masterpiece and uncovers a conspiracy that could bring the world to the brink of nuclear Armageddon. Legendary art restorer and spy Gabriel Allon joins forces with a brilliant and beautiful master-thief to track down the world's most valuable missing painting but soon finds himself in a desperate race to prevent an unthinkable conflict between Russia and the West. Silva's powerhouse novel showcases his outstanding skill and brilliant imagination, destined to be a must-read for both his multitudes of fans and growing legions of converts.